2009
DOI: 10.2215/cjn.02910608
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Brachiocephalic Fistulas, Transposed Brachiobasilic Fistulas, and Upper Arm Grafts

Abstract: Background and objectives: An upper arm vascular access is often placed in patients with a failed forearm fistula or with vessels unsuitable for a forearm fistula. The aim of this study was to compare the outcomes of three upper arm access types: brachiocephalic fistulas, transposed brachiobasilic fistulas, and grafts.Design, setting, participants, & measurements: A prospective, computerized access database was queried retrospectively to identify the clinical outcomes of upper arm accesses placed in 678 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 23 publications
10
94
2
Order By: Relevance
“…The secondary patency rate is lower than in other published series 15,16 and may reflect the co-morbid population with a high prevalence of diabetes and peripheral vascular disease (known factors associated with AVF failure). 17,18 Interestingly, nearly one-third of all BBF created were not used for HD.…”
Section: Utilization Of Avfcontrasting
confidence: 58%
“…The secondary patency rate is lower than in other published series 15,16 and may reflect the co-morbid population with a high prevalence of diabetes and peripheral vascular disease (known factors associated with AVF failure). 17,18 Interestingly, nearly one-third of all BBF created were not used for HD.…”
Section: Utilization Of Avfcontrasting
confidence: 58%
“…Use of arteries or veins ,1.5 mm in diameter is associated with higher AVF nonmaturation (53), prompting most surgeons to require arterial diameters .2 mm and venous diameters $2.5 mm. However, using even higher vascular diameters does not lower AVF nonmaturation (54). The effect of preoperative vascular diameters on AVG survival has not been reported.…”
Section: Answermentioning
confidence: 96%
“…Studies conflict regarding the association between women, AVF nonmaturation, and reduced patency (6)(7)(8)(9), which is hypothesized to be related to smaller diameter veins in women compared with men. This is difficult to assess, because many studies do not perform preoperative vein mapping or report vein diameters.…”
Section: Demographicsmentioning
confidence: 99%
“…The varying definitions of maturation, patency, and techniques of measuring vein diameter likely contribute to the wide range of threshold diameters cited. To further complicate the situation, some authors have shown that there can be substantial overlap in the vein diameters of those whose AVF fail and those that succeed (7). Vein quality (e.g., distensibility) has not been studied extensively (59)(60)(61); however, the great majority of surgeons would not use a vein that appears sclerotic on either preoperative duplex ultrasound or direct examination.…”
Section: Vein Size/qualitymentioning
confidence: 99%